ENVIRONMENTAL POLLUTION AND IMPACT OF HIGHWAYS DURING OPERATION - Nataliia Kharytonova (World Science, 2023)
The current state and rapid development of road construction and transport infrastructure are the reasons for the increase in environmental pollution, especially in the immediate vicinity of highways. Roadside areas accumulate a large amount of pollutants which leads to changes in soil properties and comprehensive degradation of landscapes. Together with the road runoff, pollutants enter the lakes and the rivers and cause significant damage to aquatic flora and fauna. During the operation of highways, a large amount of exhaust gases, oil products, heavy metals, and dust enters the natural environment. Currently, in Ukraine, most studies are aimed at reducing the negative impact of exhaust gases on the atmosphere, oil pollution of soils and the aquatic environment. Unlike in the European countries, the research on the formation of microparticles which, together with dust and surface runoff contaminate soils, surface and groundwater of roadside areas has not been conducted at all. This paper analyzes the European research experience on the negative impact of microparticles on the environment. The components of microparticles - micropollutants formed as a result of the interaction of vehicles with the road surface (tire wear products, road dust, road markings, etc.) are presented. The paper also presents the sources of formation, qualitative and quantitative characteristics of the main micropollutants and their pathways in the roadside area. This will allow further developing the effective measures to reduce the formation and spread of micr